Production of an electro-biological particle electrode (EBPE) from lithium slag and its removal performance to salicylic acid in a three-dimensional electrocatalytic biological coupling reactor (3D-EBCR). (November 2021) - Li, Xinxin; Li, Xing; Feng, Yan; Wang, Xinwei; Suo, Ning; Yang, Shumin; Long, Yingying; Zhang, Shoubin
Abstract: Electro-biological particle electrode (EBPE) prepared by lithium slag was used to remove salicylic acid in a three-dimensional electrocatalytic biological coupling reactor (3D-EBCR). The physical and chemical properties of the EBPE, the removal performance of salicylic acid and the degradation mechanism were studied. Results revealed as follows: (1) the EBPE prepared by lithium slag contained effective catalytic components including Fe2 O3, SnO2, ZnO, MnO, Rb2 O and TiO2, with stable structure and good adsorption performance; (2) the 3D-EBCR with EBPE had strong adaptability to the current intensity in the range of 0.25–0.40 A, and the removal rates of COD and salicylic acid were maintained above 87.1% and 85.2% respectively; (3) salicylic acid was removed through the synergistic action of adsorption, electrochemical oxidation and biological action. Graphical abstract: Image 1 Highlights: Electrobiological particle electrodes were prepared from waste lithium slag. The 3D-EBCR with EBPE showed excellent removals for domestic wastewater. Possible mechanism due to adsorption, electrochemical oxidation and biodegradation. The application provided a promising way in lithium slag utilization and the treatment of domestic wastewater.